Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1159/000312914
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Lifestyle of the Virophage

Abstract: <i>Objective(s):</i> We sought to better characterize Sputnik, the first isolated virophage, and to analyze its parasitic lifestyle during co-infection with Marseillevirus (a new giant virus) in <i>Acanthamoeba castellanii</i>. <i>Methods:</i> A combination of electron microscopy, immunofluorescence microscopy, and real-time PCR was used to characterize the kinetics of the viral replication cycle. RT-PCR was performed to detect RNAs inside the Sputnik virions. <i>Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
71
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 58 publications
(45 reference statements)
3
71
0
Order By: Relevance
“…Immunofluorescence performed 6 h p.i. confirmed these results and showed that the M1 viral factories produce sputnik virions (24). However, in M4, only the VF was visible, and no production of sputnik virions could be observed (Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Immunofluorescence performed 6 h p.i. confirmed these results and showed that the M1 viral factories produce sputnik virions (24). However, in M4, only the VF was visible, and no production of sputnik virions could be observed (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Sputnik is a small icosahedral virus that successfully parasitizes Mimiviridae (11). It was previously hypothesized that sputnik uses the Mimivirus fibers as a gateway to penetrate the amoeba (24). Another virophage (called sputnik 2) was recently found to be associated with a giant virus isolated from a liquid from a contact lens of a patient with keratitis (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement of Mimivirus for the propagation of Sputnik gave rise to the term "virophage" (4). EM images suggest that Sputnik virus matures in viral factories together with Mimivirus itself (5). This observation is supported by in situ hybridization experiments (6), which showed that Sputnik replicates its genome in viral factories.…”
mentioning
confidence: 95%
“…Virophages appear to have evolved multiple strategies to track down their viral and cellular hosts. The Sputnik virophage can adhere to long fibers on the surface of the mimivirus capsid, and it is assumed that Sputnik hitches a ride when mimivirus is phagocytosed by the amoebal host cell (8). By contrast, the mavirus virophage enters the host cell independently of its giant virus CroV, which lacks an external fiber coat (9).…”
mentioning
confidence: 99%